Barnyard [videorecording (Blu-Ray)] (Paramount Home Entertainment, 2022)
Move over, all pretenders. Here are the original party animals. This laugh-filled adventure stars Otis, a carefree cow who spends his days singing, dancing, and playing tricks on humans, much to the dismay of his father, Ben. Wild, wacky, and "udderly" hilarious, here's a herd of animated pranksters that'll keep viewers laughing out loud!